2010
DOI: 10.1073/pnas.1009381107
|View full text |Cite
|
Sign up to set email alerts
|

Central gating of fly optomotor response

Abstract: We study the integration of multisensory and central input at the level of an identified fly motoneuron, the ventral cervical nerve motoneuron (VCNM) cell, which controls head movements of the animal. We show that this neuron receives input from a central neuron signaling flight activity, from two identified wide-field motion-sensitive neurons, from the wind-sensitive Johnston organ on the antennae, and from the campaniform sensillae of the halteres. We find that visual motion alone leads to only subthreshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 53 publications
7
83
1
Order By: Relevance
“…Given how different the tasks of passively receiving a stimulus and active sensation are, it is not surprising that this assumption has been challenged more recently. Several pioneering studies, in vertebrates as well as insects, demonstrated that the behavioral state of an animal has a strong influence on sensory processing (Treue and Maunsell, 1996;Rind et al, 2008;Chiappe et al, 2010;Haag et al, 2010;Maimon et al, 2010;Niell and Stryker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Given how different the tasks of passively receiving a stimulus and active sensation are, it is not surprising that this assumption has been challenged more recently. Several pioneering studies, in vertebrates as well as insects, demonstrated that the behavioral state of an animal has a strong influence on sensory processing (Treue and Maunsell, 1996;Rind et al, 2008;Chiappe et al, 2010;Haag et al, 2010;Maimon et al, 2010;Niell and Stryker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While the increase in the firing rate after the application of CDM was about 3-fold, the increase associated with flying was about 6-10-fold. An increase in spontaneous activity is in accordance with work done in parallel on state-dependent influences of other lobula plate tangential cells in Drosophila and Calliphora Haag et al, 2010;Longden and Krapp, 2009;Longden and Krapp, 2010;Maimon et al, 2010;Rosner et al, 2010). In principle, four different behavioral states were investigated: application of CDM (Longden and Krapp, 2009), passive and active movement of the halteres Rosner et al, 2010), walking and flying (Maimon et al, 2010).…”
Section: The Behavioral State Changes the Level Of Spontaneous Activimentioning
confidence: 60%
“…The other behavioral states are the flight condition and the CDM application condition. In the following I will compare the findings of this study with previous work (Heide, 1983) and recent literature on the effect of the behavioral state in flies Haag et al, 2010;Longden and Krapp, 2009;Longden and Krapp, 2010;Maimon et al, 2010;Rosner et al, 2010). Heide (1983) in collaboration with his colleagues Foster and McCann also recorded from a lobula plate tangential cell which they assumed to be H1.…”
Section: State-dependent Modulation Of Visual Processing In the Flymentioning
confidence: 67%
See 2 more Smart Citations